2011
DOI: 10.5402/2011/972838
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Fluid and Glucose Transport in Wistar Rats following Chronic Consumption of Fresh or Oxidised Palm Oil Diet

Abstract: Chronic ingestion of thermoxidized palm oil causes functional derangement of various tissues. This study was therefore carried out to determine the effect of chronic ingestion of thermoxidized and fresh palm oil diets on intestinal fluid and glucose absorption in rats using the everted sac technique. Thirty Wistar rats were divided into three groups of 10 rats per group. The first group was the control and was fed on normal rat chow while the second (FPO) and third groups (TPO) were fed diet containing either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
0
8
0
1
Order By: Relevance
“…We had earlier reported that oil from palm significantly reduced the GOT and GPT increase in the liver induced by exposures to heavy metal,[828] the study then suggests that the oil from palm has a hepatoprotective role as has been highlighted by some researchers. [829]…”
Section: Discussionmentioning
confidence: 99%
“…We had earlier reported that oil from palm significantly reduced the GOT and GPT increase in the liver induced by exposures to heavy metal,[828] the study then suggests that the oil from palm has a hepatoprotective role as has been highlighted by some researchers. [829]…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vivo , in vitro , and epidemiological studies have shown few medicinal properties of PPE as an antioxidant, against colon cancer, T2DM, and inflammatory-mediated diseases ( 21 25 ). Also, PPE possesses radical-scavenging properties in diethylnitrosamine-induced liver injuries, reversed methotrexate toxicity in the liver by decreasing oxidative stress and liver apoptosis, and enhanced the activity of liver enzymes against ROS after CCl 4 toxicity ( 26 , 27 ). This study aims to explore the potential role of PPE in HFD-fed rats.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown to demonstrate genotoxic and preneoplastic change in the rat liver [10]. It also impaired fluid and glucose intestinal absorption in rats [11]. In rats given alcohol plus heated sunflower, an apparent liver damage as well as increased cholesterol level was observed [12].…”
Section: Introductionmentioning
confidence: 99%